THE EFFECT OF YOUTUBE ON SPEAKING ABILITY OF SENIOR HIGH STUDENTS - Zainal Abidin; Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2021)
YouTube is a rich source for teaching speaking in EFL contexts. You Tube also enables students to learn language of the world. The present study aimed to know whether secondary students in Indonesia who frequently watched You Tube in English speak better that than those who seldom. This was an ex-post-facto study. A questionnaire and speaking test were designed to students speaking ability. T-test and ANOVA were used to measure the different effects of You Tube. The present study revealed that the speaking ability of the subjects who watched You Tube exceeded the speaking ability of those who seldom watched You Tube. Based on the T-test analysis, YouTube gave good effect on students’ speaking ability, however based on the ANOVA analysis, You Tube gave the highest effect on the vocabulary aspect of their speaking ability.Keywords: YouTube, Speaking Skills, EFL Students